Effect of Contract Farming on the Income and Risk of Pistachio and Saffron Producers in Iran - Abarghouei, Mohammad Mehri; Borazjani, Mahmoud Ahmadpour; Mohammadi, Hamid; Salarpour, Mashallah (Revista de Ciências Agroveterinárias, 2020)
Contract farming is among the institutional arrangements essential for agricultural products. In most cases, these contracts lead to increased incomes and welfare of farmers. However, this type of business has not been taken seriously in Iran. This study aimed to analyze the effect of contract farming on the income and risk of the farmer’s income. To this end, pistachio and saffron farmers in the Yazd Province, in central Iran, were considered in the harvest year of 2017-2018. We divided the farmers into three homogeneous groups, each with different input consumption levels and production per hectare. We calibrated the cost functions of representative farmers in each group. These functions were employed to develop an ideal formal contract model and relational contract model. According to the results, formal contracts and relational contracts increased income and relational contracts reduced the risk to farmers when they were compatible with the incentive constraints of the farmer. Policymakers should provide favorable conditions for the development of contract farming. For instance, they can present contract farming to farmers and encourage agricultural enterprises to participate in contracts by facilitating access to credit and other investment incentives.